Beclin 1, LC3, and p62 expression in paraquat-induced pulmonary fibrosis. (July 2019) - Xu, G; Wang, X; Yu, H; Wang, C; Liu, Y; Zhao, R; Zhang, G
Paraquat (PQ) is a highly toxic herbicide to humans. Pulmonary fibrosis is one of the most typical features of PQ poisoning, which develops from several days to weeks after ingestion. However, the mechanism of fibrosis is still unclear. In this study, we aimed to determine expressions of autophagy-related markers Beclin 1, microtubule-associated protein light chain 3 (LC3), and p62 in PQ-poisoned lungs and to explore the role of autophagy in pulmonary fibrosis induced by PQ. We detected markers of lung fibrosis and expressions of autophagy-related protein in the specimens from eight fatal cases of PQ poisoning by hematoxylin and eosin staining, Masson's trichrome staining, and immunohistochemistry. Based on the staining results of lung fibrosis, these cases were divided into two groups, fibrosis and non-fibrosis groups. The correlation between autophagy protein expressions and pulmonary fibrosis was examined. The results demonstrated that the autophagy-related proteins were significantly expressed in fibrosis group compared with the non-fibrosis group. There was a significantly positive correlation between these protein expressions and severity of lung fibrosis. In conclusion, autophagy dysfunction may be involved in lung fibrogenesis caused by PQ poisoning. This may be a promising clue for understanding the molecular mechanism underlying PQ-induced lung fibrosis and provide evidence for treating fibrosis by regulating the level of autophagy.